Computer Science Integrations with Laser Processing for Advanced Solutions - Serguei P. Murzin (Photonics)
This article examines the role of computer science in enhancing laser processing techniques, emphasizing the transformative potential of their integration into manufacturing. It discusses key areas where computational methods enhance the precision, adaptability, and performance of laser operations. Through advanced modeling and simulation techniques, a deeper understanding of material behavior under laser irradiation was achieved, enabling the optimization of processing parameters and a reduction in defects. The role of intelligent control systems, driven by machine learning and artificial intelligence, was examined, showcasing how a real-time data analysis and adjustments lead to improved process reliability and quality. The utilization of computer-generated diffractive optical elements (DOEs) was emphasized as a means to precisely control laser beam characteristics, thus broadening the application opportunities across various industries. Additionally, the significance of predictive modeling and data analyses in enhancing manufacturing effectiveness and sustainability is discussed. While challenges such as the need for specialized expertise and investment in new technologies persist, this article underscores the considerable advantages of integrating computer science with laser processing. Future research should aim to address these challenges, further improving the quality, adaptability, and sustainability of manufacturing processes.